Anti-allergic Inflammatory Effects of the Essential Oil From Fruits of Zanthoxylum coreanum Nakai - Guo, Rui Hong; Park, Jung Up; Jo, Se Jin; Ahn, Jae Hun; Park, Jong Hwan; Yang, Ji Yoon; Lee, Sung Suk; Park, Mi Jin; Kim, Young Ran (Frontiers in Pharmacology, 2018)
Zanthoxylum coreanum Nakai is a rare shrub which grows in Korea and China. Pericarp of Zanthoxylum coreanum Nakai has been used as a crude medicine, but there are few researches about the pharmacologic activities. The present study was designed to investigate the anti-allergic inflammatory activities of the essential oil from fruits of Zanthoxylum coreanum Nakai (ZCO). Our findings showed that ZCO inhibited both the IgE-antigen complex or PMA/A23187-induced β-hexosaminidase release and IL-4 production dose-dependently in RBL-2H3 mast cells, and confirmed that ZCO at the tested concentrations did not show cytotoxicity to RBL-2H3 cells by MTS assay. Additionally, we found that ZCO showed the significant inhibition on LPS-induced overproduction of TNF-α, IL-6 and NO. Consistently, the protein levels of iNOS and COX-2 were also remarkably decreased by ZCO treatment. Herein, Our mechanistic studies revealed that ZCO significantly suppressed the activation of transcription factor NF-κB in PMA-activated 293T cells, and further inhibited NF-κB p65 translocation into the nucleus in LPS-stimulated RAW264.7 cells. Further investigation identified that ZCO down-regulated LPS-induced phosphorylation of MAPK (JNK, ERK, and p38) signal pathway. For incremental research, we established an DNCB-induced atopic dermatitis model in BALB/c mice, and found that ZCO remarkably inhibited DNCB-induced ear swelling and AD-like symptoms. Based on these findings, ZCO is suggested to have a therapeutic potential for the allergic inflammatory diseases.